Asymptotic Properties of Solutions to Second-Order Difference Equations of Volterra Type - Janusz Migda; Małgorzata Migda; Magdalena Nockowska-Rosiak (Discrete Dynamics in Nature and Society)
We consider the discrete Volterra type equation of the form Δ(rnΔxn)=bn+∑k=1nK(n,k)f(xk). We present sufficient conditions for the existence of solutions with prescribed asymptotic behavior. Moreover, we study the asymptotic behavior of solutions. We use o(ns), for given nonpositive real s, as a measure of approximation.